Drug Discovery and its Applications - Jadhav, Suraj Suresh; Rohane, Dr.S.H.; Redasani, Dr.V.K. (Asian Journal of Pharmaceutical Research and Development, 2024)
The document provides a comprehensive overview of organic and inorganic chemistry, drug design and discovery, and medicinal chemistry. It defines organic and inorganic compounds, highlighting their structural differences and properties. Additionally, it outlines current good laboratory practices (GLP) and regulatory aspects associated with chemical research and development. In the realm of drug design and discovery, the document emphasizes the complex process involved, spanning identification, synthesis, validation, and optimization of potential drug candidates. Various techniques such as computer-aided drug design (CADD), molecular docking, quantitative structure-activity relationship (QSAR), and prediction of absorption, distribution, metabolism, and excretion (ADME) parameters are discussed. The section on medicinal chemistry delves into the interdisciplinary nature of the field, combining aspects of organic chemistry, pharmacology, and biology. It explores the historical development of medicinal agents and the role of regulatory agencies in ensuring drug safety and efficacy. Overall, the document highlights the skills acquired, including the ability to differentiate between organic and inorganic compounds, knowledge of regulatory practices, proficiency in using chemical modelling tools for prediction, and understanding of drug design processes. It provides a holistic understanding of the theoretical foundations, practical applications, and regulatory considerations within these interconnected fields.